Cardiorespiratory fitness, screen time and cardiometabolic risk in South Brazilian school children - Debora Tornquist; Luciana Tornquist; Ana Paula Sehn; Letícia de Borba Schneiders; Jane Dagmar Pollo Renner; Silvia Isabel Rech Franke; Cézane Priscila Reuter; Roya Kelishadi (Annals of Human Biology, 2022)
Background Cardiorespiratory fitness (CRF) is considered a beneficial effect of physical activity (PA). PA and excessive screen time have implications for cardiometabolic risk. Objective To verify the association between screen time and CRF grouped by cardiometabolic risk factors. Subjects and methods Cross-sectional study evaluated 1,253 schoolchildren (54.2% girls) aged seven to 17 years from southern Brazil. The outcomes were body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), and diastolic (DBP), glucose, and lipid profile. Exposure was a combined variable of self-reported screen time (television, video game, computer) and CRF. Results The main result is that CRF had a more consistent association with anthropometric factors than with metabolic variables. Low CRF students, regardless of screen time, showed a 15% increase in the risk of elevated WC (p < 0.001) and a 24% (<2 h screen time) and 19% (≥2 h) higher risk of overweight (p < 0.001). Second, the increase in SBP was associated with a combination of the two risk factors, ≥2 h screen time/low CRF was associated with a 7% increase in elevated SBP (p = 0.025). Conclusion Low CRF was a risk factor for elevated BMI and WC, regardless of screen time. High screen time and low CRF were associated with higher SBP values.